Effects of rain intensity variation on rain attenuation prediction for Free Space Optics (FSO) links - Ahmad Zabidi, Suriza; Islam, Md. Rafiqul; Al-Khateeb, Wajdi Fawzi Mohammed; Naji, Ahmed Wathik (2012)
Free Space Optics (FSO) link have capabilities of providing optical communications similar to fiber optics based communications. However, the operational status of an FSO link is highly weather dependent which hampered the FSO link with feasibility issue. Among the major effect on FSO links under local weather condition is due to attenuation of heavy rainfall. Attenuation due to rainfall can restrict the path length of communication systems at frequencies above 10 GHz. The studies on the effect of rain intensity variation have been proposed by many models based on the radio wave propagation at centimeter or millimeter wavelength. Among the models are Lin Model, Moupfouma Model, Assis Model, Dissanayake and Allnutt Model, ITU Model, Abdulrahman Model and Silva Mello Model. The objective of this research to investigate the effect of rain intensity variation on the rain attenuation prediction for FSO links.